Feed selection and nutrient utitization by Jamunapari and Barbari goats on synthesized silvipasture - SHARMA, K; SAINI, A L; SINGH, NAWAB; OGRA, J L (The Indian Journal of Animal Sciences, 2013)
Distinct differences were observed in the grazing behaviour and feed selection pattern of 6 each of Jamunapari and Barbari goats kept on a reconstituted pasture comprising Leucaena leucocephata, Dichroslachys nulan and Cenchrus ciliaris during later half of rainy season. Though a diurnal pattern of feeding was observed in both the breeds, Barbari goats spent significantly more time (481 min) on active foraging compared to Jamunapari (277 min). While Barbari goat, spent 76% of their foraging time on ground flora, Jamunapari preferred browsmg and spent only 27.8% of their time on grasses. A panicular liking of goats was towards plant parts higherin nutritive value. No breed difference was, however, evident in the proximate composition, DM intake and nutrient digestibility of ingested herbage. It appears that variability in grazing preference between goal breeds in a multi-tierpasture does not necessarily bring about change In the intake and nutrient utilization of ingested herbage.